A torque analysis of permanent magnet brushless DC motor for driving electric vehicles - Kasturi Ramachandran (Universiti Malaysia Perlis, 2009)
This final year project presents a torque analysis of permanent magnet brushless DC motor (PMBDC) for driving electric vehicles (EV) using MATLAB programming as a tool to study on the dynamic performance of the motor. Electric vehicles system is an integration of vehicle body, electric propulsion, energy storage battery and energy management. It more advances because its energy independence, limit energy cost, and environmental protection. PMBDC motor is most promising motor used in electric vehicles because it can produce large torque at the same peak current and voltage due to interaction between rectangular current and rectangular magnetic field. Therefore analyze on the characteristic of PMBDC motor to see its performance in electric vehicle is needed. The characteristic of PMBDC motor include its torque performance, speed, input current, the torque angle and its efficiency. This final project begins with the development of the state space model which is then converted to discrete time by using trapezoidal algorithm. Finally the equations are verified by using simulation of MATLAB programming to study dynamic performance of PMBDC motor. From the result, speed and torque are depends on the phase current of stator where changes on phase current influence the starting torque value of PMBDC motor.